Downregulation of a putative tumor suppressor BMP4 by SOX2 promotes growth of lung squamous cell carcinoma. Issue 4 (30th January 2014) - Fang, Wen‐Tsen; Fan, Chi‐Chen; Li, Shih‐Miao; Jang, Te‐Hsuan; Lin, Hsiu‐Ping; Shih, Neng‐Yao; Chen, Chung‐Hsing; Wang, Tao‐Yeuen; Huang, Shiu‐Feng; Lee, Alan Yueh‐Luen; Liu, Ying‐Lan; Tsai, Fang‐Yu; et al.
<x xml:space="preserve">Abstract</x> SOX2 is a transcription factor essential for self‐renewal and pluripotency of embryonic stem cells. Recently, SOX2 was found overexpressed in the majority of the lung squamous cell carcinoma (SQC), in which it acts as a lineage‐survival oncogene. However, downstream targets/pathways of SOX2 in lung SQC cells remain to be identified. Here, we show that BMP4 is a downstream target of SOX2 in lung SQC. We found that SOX2‐silencing‐mediated inhibition of cell growth was accompanied by upregulation of BMP4 mRNA and its protein expression. Meta‐analysis with 293 samples and qRT‐PCR validation with 73 clinical samples revealed an inversely correlated relationship between levels of SOX2 and BMP4 mRNA, and significantly lower mRNA levels in tumor than in adjacent normal tissues. This was corroborated by immunohistochemistry analysis of 35 lung SQC samples showing lower BMP4 protein expression in tumor tissues. Cell‐based experiments including siRNA transfection, growth assay and flow cytometry assay, further combined with a xenograft tumor model in mice, revealed that reactivation of BMP4 signaling could partially account for growth inhibition and cell cycle arrest in lung SQC cells upon silencing SOX2. Finally, chromatin immunoprecipitation analysis and luciferase reporter assay revealed that SOX2 could negatively regulate BMP4 promoter activity, possibly through binding to the promoter located in the first intron region of BMP4. Collectively, our findings suggest that BMP4 could act as a tumor suppressor and its downregulation by elevated SOX2 resulting in enhanced growth of lung SQC cells.